Developing Iranian EFL Learners’ Grammatical Knowledge: Insights from Spaced versus Massed Instruction - Behbahani, Hossein Kargar; Darazi, Mansoor Ali; Kumari R, Lakshmi (JOLLT Journal of Languages and Language Teaching, 2024)
Despite grammar receiving greater emphasis than other language skills in Iranian schools, Iranian EFL students encounter challenges in acquiring the linguistic structures they are exposed to, resulting in insufficient grammar knowledge. This experiment looked into the effects of spaced versus massed instruction on learning modal auxiliaries among Iranian EFL learners with a lower-intermediate command of English. To this end, through an Oxford Quick Placement Tests (OQPT), 78 lower-intermediate learners were selected and assigned in three conditions, with 26 subjects in each: Spaced condition, Massed condition, Control condition. Using a Levene’s test, it was shown that the subjects were homogenous prior to the experiment. Then, a pretest was used. The results of the pretest showed that there was no between groups’ difference prior to the treatment. Afterward, the spaced group received three 30-minute sessions on modal auxiliaries based on Fundamentals of English Grammar by Azar (2016), while the massed condition received the instruction in just a single 90-minute session. The subjects in all conditions were then posttested. The results of a one-way between groups analysis of variance (ANOVA) showed that both treatment groups outperformed the comparison group (p < .05) with a large effect size (eta squared = .63). The results of post-hoc analyzes using Bonferroni adjustment further revealed that there was a statistically significant difference between the two experimental conditions (p < .05). That is, the spaced subjects gained more compared to their massed counterparts with regard to the targeted L2 form. Pedagogically, this study suggests ESL/EFL instructors could integrate spaced instruction strategies for enhancing students' proficiency in modals. Material developers may also leverage these findings to create more engaging and effective instructional materials.